The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1021/ie3036096
|View full text |Cite
|
Sign up to set email alerts
|

Polysulfone/Vanillin Microcapsules for Antibacterial and Aromatic Finishing of Fabrics

Abstract: Microencapsulation technology is being more and more applied in the textile industry because microcapsules can confer additional properties to conventional fabrics. In this context, polysulfone microcapsules containing vanillin were prepared, and their morphology, thermal stability, and antibacterial properties against Staphylococcus aureus were assessed. The microcapsules were fabricated onto 100% cotton fabrics by a coating technique. The resistance of the coating to several washing cycles was studied, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 53 publications
0
40
0
Order By: Relevance
“…The pharmacological investigation [24] has proved that vanilla is of excellent biological activity, and can even be used by the injection of an effective dose amount [25] . Vanillin suppresses metastatic potential of human cancer cells via PI3K inhibition, decreases angiogenesis in vivo [26] and exhibits antibacterial and antimicrobial activities [27,28] . The latest research showed that vanillin elevated both serotonin and dopamine levels in brain tissue and could alleviate depressive symptoms in the rat model of chronic depression via the olfactory pathway [29] .…”
Section: Introductionmentioning
confidence: 99%
“…The pharmacological investigation [24] has proved that vanilla is of excellent biological activity, and can even be used by the injection of an effective dose amount [25] . Vanillin suppresses metastatic potential of human cancer cells via PI3K inhibition, decreases angiogenesis in vivo [26] and exhibits antibacterial and antimicrobial activities [27,28] . The latest research showed that vanillin elevated both serotonin and dopamine levels in brain tissue and could alleviate depressive symptoms in the rat model of chronic depression via the olfactory pathway [29] .…”
Section: Introductionmentioning
confidence: 99%
“…The experiments were conducted in a commercial washing machine (Bosch Maxx WFO-2063). As can be observed, the number of capsules decreased every washing cycle (see Table 4.3, extracted from a previous study [24]). The laundry program was intended to be as close as possible to the standard normal home laundry test conditions fixed by the American Association of Textile Chemists and Colorists.…”
Section: Microcapsules Adhesion To Fabricsmentioning
confidence: 58%
“…A modified agar-well diffusion technique was employed [47] and petri dishes containing 15 mL of nutrient agar were filled with a mixture of 100 µL of standard 108 colony forming unit (CFU)/mL S. aureus. According to the published results [24], the inhibition diameter remain constant for at least 1 week, which means that PSf/vanillin microcapsules inhibited S. aureus for at least 1 week, showing promising results for the inhibition of the bacteria growth. Similar results had been previously reported [13].…”
Section: Antibacterial Activitymentioning
confidence: 77%
See 1 more Smart Citation
“…Textile manufacturers are demonstrating particularly interest in the application of durable fragrances to textile as well as skin softeners [2]. In this context, microencapsulation technology is a growing area in textile industry [3]. Microencapsulation is a technique of surrounding solid, liquid or gas particles with a continuous film or polymeric material ranging in size from 1 µm to 1 mm.…”
Section: Introductionmentioning
confidence: 99%